The elite young athlete: strategies to ensure physical and emotional health - Sabato, T. M.; Walch, T. J.; Caine, D. J. (Open Access Journal of Sports Medicine, 2016)
This article presents a current review of the risk of physical and psychological injury associated with participation in elite youth sport, and suggests strategies to ensure the physical and emotional health of these young athletes. Although there is lack of epidemiological data, especially with regard to psychological injury, preliminary data suggest that the risk of injury is high in this population. While there is lack of incident and follow-up data, there is also concern regarding burnout, disordered eating, and the long-term consequences of injury. Modifiable injury risk factors identified include postural control, competition anxiety, life events, previous injury, and volume of training. There are presently no studies designed to determine the effectiveness of injury prevention measures in elite youth sports. However, there is adequate evidence arising from injury prevention studies of youth sports participants - including neuromuscular training, protective equipment, mental training to enhance self-esteem, and sport rules modification - to prevent injuries in elite youth sports settings. Although not tested, psychosocial prevention strategies such as adoption of task-oriented coping mechanisms, autonomous support from parents, and a proactive organizational approach also show promise in injury prevention